An experimental and numerical investigation of the ballistic penetration behavior and failure mechanism of 3D MWK composites. (1st November 2022) - Zhu, Hao; Li, Dian-sen; Jiang, Lei; Fang, Dai-ning
Abstract: 3D multi-axial warp knit (MWK) composites have been gradually focused on the aeronautics and astronautics fields. This paper carried out ballistic penetration experiment of 3D MWK carbon/epoxy composites with blunt projectile to obtain ballistic penetration behaviors and failure mechanisms. Meanwhile, an elasto-plastic constitutive model was established to predict the damage evolution and absorbed energy, where strain rate effect and interface behavior were considered simultaneously. A sensitivity analysis of ballistic penetration properties to impact velocity was thoroughly analyzed. The experimental data were compared with the numerical prediction results. The results convincingly concluded that the ballistic penetration properties strongly depended on the impact velocity. With the increase of impact velocity, the energy absorption capacity of the composite was strengthened, and yarn breakage and resin plasticization were more severe. The numerical predicted results were well in conjunction with the experimental data, proving that the ballistic penetration behaviors could be accurately predicted.